2022
DOI: 10.1021/acs.inorgchem.1c03853
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Probing of Size-Selective Crown Ether Macrocycle Ligands for Transplutonium Element Separation

Abstract: Effective separation and recovery of chemically similar transplutonium elements from adjacent actinides is extremely challenging in spent fuel reprocessing. Deep comprehension of the complexation of transplutonium elements and ligands is significant for the design and development of ligands for the in-group separation of transplutonium elements. Because of experimental difficulties of transplutonium elements, theoretical calculation has become an effective means of exploring transplutonium complexes. In this w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 54 publications
(77 reference statements)
0
20
0
Order By: Relevance
“…The delocalization index (DI) of the M−N bond can be used as a measure of the electron sharing between the N and M basins. A higher value of DI indicates more electron sharing between the two basins and generally a stronger bond between the two bonded atoms [24] . According to Table 1, the donor N atom of the ligands shares more electrons with Am than with Eu, so forms a stronger bond with Am than with Eu.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The delocalization index (DI) of the M−N bond can be used as a measure of the electron sharing between the N and M basins. A higher value of DI indicates more electron sharing between the two basins and generally a stronger bond between the two bonded atoms [24] . According to Table 1, the donor N atom of the ligands shares more electrons with Am than with Eu, so forms a stronger bond with Am than with Eu.…”
Section: Resultsmentioning
confidence: 99%
“…A higher value of DI indicates more electron sharing between the two basins and generally a stronger bond between the two bonded atoms. [24] According to Table 1, the donor N atom of the ligands shares more electrons with Am than with Eu, so forms a stronger bond with Am than with Eu. For the same metal, the N donor atom of the ligands L b and L c with the electron-withdrawing group shares less electrons with the metal, while the N atom of the ligands L d and L e with the electron-donating group shares more electrons with the metal, consistent with the above analysis.…”
Section: Chemistryselectmentioning
confidence: 99%
“…Thus, theoretical computational simulation is an alternative. 14,15 Furthermore, a full understanding of the fundamental physicochemical properties of actinide complexes at the atomic scale also plays a key role in describing the behavior of actinides in solution.…”
Section: Introductionmentioning
confidence: 99%
“…This method has fewer limiting factors compared to alternative approaches and is therefore widely used. However, due to the high radioactivity and chemical toxicity of actinides, experimental study of the chemical behavior of actinides in an aqueous solution is not only difficult to conduct but also costly. Thus, theoretical computational simulation is an alternative. , Furthermore, a full understanding of the fundamental physicochemical properties of actinide complexes at the atomic scale also plays a key role in describing the behavior of actinides in solution.…”
Section: Introductionmentioning
confidence: 99%
“…A valuable approach for the recovery of REEs is the use of multifunctional ligands, which can selectively separate lanthanide or actinide cations or a mixture of both. These ligands were specifically engineered to express different metal-to-ligand interaction geometries and strengths for a specific metal–ligand entity. In a slightly different approach, Bogart et al showed that dysprosium and neodymium preferentially formed monomeric and dimeric entities, respectively, when using a polydentate N′N3O3 donor ligand.…”
Section: Introductionmentioning
confidence: 99%